A Study of Stock Market Investors of Delhi-A Behavioural Finance Perspective - Siddiqui, Saif (Indian Journal of Finance, 2008)
People trade for both cognitive and emotional reasons. They trade because they think they have information when they have nothing but noise, and they trade because trading can bring the joy of pride. Trading brings pride when decisions turn out well, but it brings regret when decisions do not turn out well. Investors try to avoid the pain of regret by avoiding the realization of losses, employing investment advisors as scapegoats, and avoiding stocks of companies with low reputations.